LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK DEEP BREATHING UNTUK MENGURANGI KECEMASAN AKADEMIK PADA PESERTA DIDIK SMAN 1 MARGAASIH - Dida Wida Ningsih; Tita Rosita; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
Academic anxiety occurs a lot in students, especially when facing exams. This willinterferewiththeprocessofconductingtheexamandwillhaveanimpactontheresults.The purpose of this study was to determine the profile, effectiveness and process ofimplementing group guidance services through deep breathingtechniques to reduceacademic anxiety in students of SMAN 1 Margaasih. This research uses the Mix Methodmethodwith an explanatory Sequential design. The subjects in this study were grade Xstudents of SMAN 1 Margaasih with a population of 128 students and a sample of 16students.Quantitativedatacollectionusedacademicanxietyquestionnaireswhenfacingexams,whilequalitativedatacollectionwascarriedoutbyconductinginterviews,observations and documentation studies. The results of the study obtained data on theacademic anxiety profile of students when facing exams were in the medium categoryboth overall, gender and aspects. The process of implementing group guidance servicesthrough deep breathing techniqueswent well and had an influence on students who sawthattherewasanaveragedifferenceinpre-testandpost-testresults,withthet-testresultsshowing that the t-value was 4.479 with sig. 0.003 in the experimental group and t was3.767 with sig. 0.007 in the control group. In addition, it can also be seen in the resultsof interviews with students who are characterized by students having different views onexams,beingabletofaceexamscalmly,confidentlyandunderstandinghowtoovercomeanxiety when facing exams.